NOTARY PUBLIC RESPONSIBILITY IN REPORTING SUSPECTED MONEY LAUNDERING CRIMES UNDER INDONESIAN LAW - Munik, Apriyas; Hamidi Masykur, Mohammad; M Sudirman, M Sudirman; Jameela, Mariyam (Faculty of Law, Universitas Pekalongan, 2025)
Money laundering is a serious crime that threatens the integrity of Indonesia's legal and financial systems. In practice, notaries, as public officials authorized to draw up authentic deeds, are often in a strategic position that can potentially be exploited as a means of money laundering. Therefore, notaries are burdened with the responsibility of reporting suspected money laundering crimes as part of the regime for the prevention and eradication of money laundering crimes. This study aims to analyze the form of notary responsibility in reporting suspected money laundering crimes and their legal implications according to Indonesian law. The research method used is normative juridical with a legislative and conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that the responsibilities of notaries in reporting suspected money laundering crimes have been regulated in various laws and regulations, but still raise normative issues, particularly regarding the limits of reporting obligations, the principle of professional secrecy, and legal certainty and protection for notaries. Therefore, regulatory clarity and synchronization of regulations are needed to ensure the effective implementation of notaries' responsibilities without neglecting the principles of prudence and legal protection.